Bullying y cyberbullying: intervenciones realizadas en el contexto escolar - Tristão, Laura Aparecida (2022)
There are gaps concerning the dissemination of school-based antibullying interventions in the Latin American context. For this reason, the objective was to conduct a systematic literature review to analyze the results of initiatives intended to prevent or decrease the occurrence of bullying and cyberbullying. A bibliographic search was conducted in LILACS, PsycINFO, SciELO, SCOPUS, and Web of Science. Only school-based randomized clinical trials conducted were included. Nine studies classified as having high methodological quality were included. This review synthesizes knowledge reported by studies conducted in various countries and clarifies the limitations and contributions of experimental programs focused on students, parents, and school staff, enabling reflections regarding future interventions.